Influence of electron-donor additive on properties of plastic scintillator - Zhmurin, P.N.; Titskaya, V.D.; Bedrik, A.I.; Elyseev, D.A.; Soldysheva, E.A.; Lebedev, V.N.; Pereymak, V.N.; Adadurov, A.F. (Functional Materials, 2014)
The main goal of the work is to study the influence of electron-donor additives of a polymer matrix on scintillation properties of plastic scintillators. Molecules of triphenylamine were chosen as the additives which have substantially lesser than styrene ionization. The use of this compound leads to distinct improving of the scintillator properties, namely, to increasing the light yield on 15 % and cutting in half the rise time.